Personal Finance Management Behavior and Green Innovation Technology: Is it able to drive The Green Economic Sustainability? - Rita Andini,; Dimas Adi Wicaksono,; Ahmad Dwi Nurdiyanto,; Hesti Ristanto, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The transition from conventional energy use to green energy has its challenges. On the other hand, it is important for society to further review the potential use of electric transportation in an effort to reduce air pollution. This study aims to explore the determinants of factors that impact a sustainable green economy based on personal financial management behavior and green technology innovation. In addition, this study seeks to build a new basic model to fill the limitations of previous studies. Quantitative methods were chosen in this study to represent the phenomenon of a sustainable green economy. Data was obtained through distributing 136 questionnaires using simple random and snowball sampling techniques. Based on the findings, there is a role of personal financial management behavior to strengthen the influence of financial knowledge on a sustainable green economy and there is no indirect influence through green technology innovation. It is necessary to explore independent variables in further similar research, in order to build a new basic model concept and alternative solutions in an effort to optimize a sustainable green economy.